if sn =2n²+3n , then d =
Answers
Answered by
9
Sum=
![\frac{(2a - d)n + d {n}^{2} }{2} = 2 {n}^{2} + 3n \\ \: comparing \: both \: sides \\ \frac{d}{2} = 2 \\ d = 4 \frac{(2a - d)n + d {n}^{2} }{2} = 2 {n}^{2} + 3n \\ \: comparing \: both \: sides \\ \frac{d}{2} = 2 \\ d = 4](https://tex.z-dn.net/?f=+%5Cfrac%7B%282a+-+d%29n+%2B+d+%7Bn%7D%5E%7B2%7D+%7D%7B2%7D+++%3D+2+%7Bn%7D%5E%7B2%7D++%2B+3n+%5C%5C++%5C%3A+comparing+%5C%3A+both+%5C%3A+sides+%5C%5C++%5Cfrac%7Bd%7D%7B2%7D++%3D+2+%5C%5C+d+%3D+4)
Answered by
5
hope it helpss........ :)
Attachments:
![](https://hi-static.z-dn.net/files/d37/11f3d7640f11772f33b5be036dcd7761.jpg)
Similar questions
Computer Science,
8 months ago
Math,
8 months ago
Environmental Sciences,
8 months ago
Math,
1 year ago
Environmental Sciences,
1 year ago
Math,
1 year ago
Computer Science,
1 year ago